Ubiquitin-immunoreactive structures in the midbrain of methamphetamine abusers - Quan, Li; Ishikawa, Takaki; Michiue, Tomomi; Li, Dong-Ri; Zhao, Dong; Oritani, Shigeki; Zhu, Bao-Li; Maeda, Hitoshi (Legal medicine, 2005)
Ubiquitin (Ub) is involved in neurodegeneration and various stress responses in the brain. The present study investigated the Ub-immunoreactive structures in the midbrain of methamphetamine (MA) abusers as a marker of drug-induced neurodegeneration. Medico-legal autopsy cases were examined: fatal MA intoxication ( n=14), other fatalities of MA abusers ( n=23) including those due to injuries, asphyxiation, drowning, fire and natural diseases, and control groups ( n=260). In the motor nervous systems, MA abusers showed a mild increase in the diffuse-type nuclear Ub-positivity in the pigmented neurons of the substantia nigra, depending on the blood MA level and irrespectively of the immediate causes of death. The intranuclear inclusion-type Ub-positivity of the nigral neurons and the granular ‘dot-like’ Ub-immunoreactivity area in the crus cerebri (cortico-spinal tracts) were usually low in MA abusers, and any increases were related to the immediate causes of death and the age of subjects. Acute MA fatality showed a higher neuronal Ub-positivity in the midbrain periaqueductal gray matter (PGM), which is involved in processing pain, fear and anxiety, and regulation of respiration and circulation. These findings suggest dysfunction of the nigral dopaminergic neurons and PGM neurons in the midbrain in MA abuse, which may account for the clinical symptoms.